Tailoring dialysis and resuming low‐protein diets may favor chronic dialysis discontinuation: Report on three cases. Issue 3 (1st May 2014) - Piccoli, Giorgina Barbara; Guzzo, Gabriella; Vigotti, Federica Neve; Capizzi, Irene; Clari, Roberta; Scognamiglio, Stefania; Consiglio, Valentina; Aroasio, Emiliano; Gonella, Silvana; Veltri, Andrea; Avagnina, Paolo
Abstract Renal function recovery (RFR), defined as the discontinuation of dialysis after 3 months of replacement therapy, is reported in about 1% of chronic dialysis patients. The role of personalized, intensive dialysis schedules and of resuming low‐protein diets has not been studied to date. This report describes three patients with RFR who were recently treated at a new dialysis unit set up to offer intensive hemodialysis. All three patients were females, aged 73, 75, and 78 years. Kidney disease included vascular‐cholesterol emboli, diabetic nephropathy and vascular and dysmetabolic disease. At time of RFR, the patients had been dialysis‐dependent from 3 months to 1 year. Dialysis was started with different schedules and was progressively discontinued with a "decremental" policy, progressively decreasing number and duration of the sessions. A moderately restricted low‐protein diet (proteins 0.6 g/kg/day) was started immediately after dialysis discontinuation. The most recent update showed that two patients are well off dialysis for 5 and 6 months; the diabetic patient died (sudden death) 3 months after dialysis discontinuation. Within the limits of small numbers, our case series may suggest a role for personalized dialysis treatments and for including low‐protein diets in the therapy, in enhancing long‐term RFR in elderly dialysis patients.